Does corporate governance structure matter for firm financial performance? A system GMM panel analysis for Vietnam - Pham, Duc Anh; Hoang, Thi Phuong Anh (Journal of International Economics and Management, 2022)
This paper investigates the impact of governance characteristics on financial performance of companies listed on the Ho Chi Minh Stock Exchange. By employing the system generalized method of moments estimator and a panel dataset covering 152 firms over the period from 2011 to 2016, our results indicate that corporate governance characteristics namely the size of board and block-holder ownership, affect the financial performance of Vietnamese firms. Surprisingly, no statistically significant evidence is found concerning the impact of other characteristics such as board gender diversity, CEO duality and non-executive director representation on firm performance.